Endoscopic ultrasound‐guided fine‐needle biopsy for the diagnosis of gastric metastasis from breast cancer mimicking primary linitis plastica: A case report. Issue 1 (5th April 2022) - Yamada, Kenta; Kaneko, Junichi; Watahiki, Moeka; Ida, Yuya; Koda, Megumu; Fukita, Kyoichi; Takeshita, Yu; Takahashi, Kenichi; Takinami, Masaki; Tsuji, Atsushi; Nishino, Masafumi; Takahashi, Yurimi; et al.
Abstract: For gastric lesions in a patient with a history of breast cancer, it is essential to distinguish between primary gastric cancer and gastric metastasis from breast cancer. However, gastric metastasis from breast cancer often mimics primary linitis plastica, and histological diagnosis may be difficult with conventional endoscopic biopsies. Herein, we describe the case of a 75‐year‐old woman who presented at our hospital with epigastralgia and vomiting. She had a history of mastectomy for carcinoma of the right breast and had received hormone therapy as adjuvant therapy. Computed tomography at arrival showed thickening of the gastric wall at the antrum and peritoneal dissemination. Esophagogastroduodenoscopy showed mucosal swelling of the antrum and stenosis of the pylorus, and histological diagnosis failed with conventional endoscopic biopsies. Endoscopic ultrasound‐guided fine‐needle biopsy using a Franseen needle was performed, and a diagnosis of gastric metastasis from breast cancer was made. She received hormone therapy and chemotherapy after deployment of a metallic stent for gastric outlet obstruction. To the best of our knowledge, this is the first case of gastric metastasis from breast cancer diagnosed using endoscopic ultrasound‐guided fine‐needle biopsy.